Muography of different structures using muon scattering and absorption algorithms. (28th January 2019) - Vanini, S.; Calvini, P.; Checchia, P.; Rigoni Garola, A.; Klinger, J.; Zumerle, G.; Bonomi, G.; Donzella, A.; Zenoni, A.
Abstract : In recent decades, muon imaging has found a plethora of applications in many fields. This technique succeeds to infer the density distribution of big inaccessible structures where conventional techniques cannot be used. The requirements of different applications demand specific implementations of image reconstruction algorithms for either multiple scattering or absorption–transmission data analysis, as well as noise-suppression filters and muon momentum estimators. This paper presents successful results of image reconstruction techniques applied to simulated data of some representative applications. In addition to well-known reconstruction methods, a novel approach, the so-called μCT, is proposed for the inspection of spent nuclear fuel canisters. Results obtained based on both μCT and the maximum-likelihood expectation maximization reconstruction algorithms are presented. This article is part of the Theo Murphy meeting issue 'Cosmic-ray muography'.